Understanding significance tests (simulation-based) (mathematica didactica, 2025)
Data literacy also includes skills for interpreting data, for example with the help of significance tests. However, there are many misconceptions about the meaning of significance tests. As part of a course for gifted students, inferential statistical methods were taught (simulation-based with R). The post-test shows: While the students can qualitatively assess after the workshop what it means when the p-value falls below the significance level, many are still subject to the so-called relevance fallacy. Finally, suggestions for the further development of the workshop are presented.